Aberrant interactions of cortical networks in chronic migraine: A resting-state fMRI study. (28th May 2019) - Coppola, Gianluca; Di Renzo, Antonio; Petolicchio, Barbara; Tinelli, Emanuele; Di Lorenzo, Cherubino; Parisi, Vincenzo; Serrao, Mariano; Calistri, Valentina; Tardioli, Stefano; Cartocci, Gaia; Schoenen, Jean; Caramia, Francesca; et al.
Abstract : Objective: We investigated resting-state (RS)-fMRI using independent component analysis (ICA) to determine the functional connectivity (FC) between networks in chronic migraine (CM) patients and their correlation with clinical features. Methods: Twenty CM patients without preventive therapy or acute medication overuse underwent 3T MRI scans and were compared to a group of 20 healthy controls (HC). We used MRI to collect RS data in 3 selected networks, identified using group ICA: the default mode network (DMN), the executive control network (ECN), and the dorsal attention system (DAS). Results: Compared to HC, CM patients had significantly reduced functional connectivity between the DMN and the ECN. Moreover, in patients, the DAS showed significantly stronger FC with the DMN and weaker FC with the ECN. The higher the severity of headache, the increased the strength of DAS connectivity, and the lower the strength of ECN connectivity. Conclusion: These results provide evidence for large-scale reorganization of functional cortical networks in chronic migraine. They suggest that the severity of headache is associated with opposite connectivity patterns in frontal executive and dorsal attentional networks.